A CASE REPORT ON DIGOXIN INTOXICATION IN A CLINICAL PHARMACIST'S PERSPECTIVE - Punniyakotti, Saranya; N, Benazeer Begum (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â  Context: Digoxin is a commonly used inotropic drug that has a narrow therapeutic range and is monitored poorly for its plasma concentration. It is commonly used in the management of cardiovascular disorders for its inotropic effects. Increased risk of chronic digoxin toxicity among the patients receiving digoxin pharmacotherapy is related to its narrow therapeutic range. Apart from its inotropic properties, it can also produce chronotropic and dromotropic effect. Its serum levels vary due to changes in body weight, age, renal function, hepatic impairment, and concomitant drug administrations. Patients receiving digoxin should be monitored periodically for potential drug interactions, adverse effects, toxicity, and other drug-related problems. Symptoms of digoxin-induced cardiotoxicity are difficult to be identified and may become fatal too. Therapeutic drug monitoring will play a significant role in reducing such drug therapy problems and will ensure safety and efficacy of the given drug. Case Report: We report a case of chronic digoxin toxicity in a 22-year-old male with congestive cardiac failure - Class IV and atrial fibrillation with ventricular bigeminy. Results: Patient's renal parameters were elevated and among electrolytes, sodium level was decreased and potassium level was increased. A reduction in the volume of the distribution of digoxin, due to impairment of renal function or congestive cardiac failure, might be one of the reasons for digoxin toxicity. Drug therapy problems (DTPs) such as untreated indication, inappropriate drug therapy, potential major drug-drug interactions, and drugs prescribed when contraindicated were observed. Conclusion: Monitoring digoxin drug therapy can bring down the risk of digoxin intoxication.